Peningkatan Produktivitas Guru SMK melalui Kreativitas Pembuatan Bahan Ajar E-Learning - Ferawati Ferawati; Fiqih Hana Saputri; Nunung Nurmaesah (Sasambo: Jurnal Abdimas (Journal of Community Service), 2022)
Perkembangan materi e-learning yang mengikuti perkembangan teknologi yang masih terbatas dan materi yang digunakan guru dalam kegiatan pembelajarannya terbatas pada buku untuk siswa dan buku untuk guru. Hal ini berdasarkan hasil survei yang telah dilakukan di SMK Bina Mandiri bahwa belum menggunakan e-learning.  Upaya dan tindakan yang sesuai dengan situasi saat ini diperlukan berupa pelatihan dan pendampingan yang harus diberikan untuk mengatasi permasalahan mitra. Kegiatan ini bertujuan agar para guru dapat membuat materi e-learning berdasarkan keahliannya. Metode dalam pelaksanaan pengabdian ini terdiri dari tahap perencanaan, pelaksanaan dan evaluasi. Kegiatan pengabdian ini diikuti oleh 13 guru-guru di SMK Bina Mandiri dan dilaksanakan pada tanggal 15 sampai 20 Agustus 2022 selama 5 (lima) hari secara luring berupa suatu pelatihan dan pendampingan. Hasil kegiatan pengabdian ini pendampingan dan pelatihan untuk menggunakan aplikasi e-learning. Kegiatan pengabdian ini terlaksana dengan baik berdasarkan hasil Kegiatan pengabdian ini terlaksana dengan baik terbukti dengan adanya pengabdian setelah kegiatan selesai. Selain itu, peserta kegiatan masih membutuhkan pelatihan serupa dengan menggunakan aplikasi e-learning jenis lain. Increasing the Productivity of Vocational High School Teachers to Increase Potential in Facing the Digital Economy through Creativity in Making E-Learning Teaching Materials  The competence of teachers in developing current e-learning teaching materials following technological developments is still very limited, and the teaching materials used by teachers in learning activities are only limited to student books and teacher books. Efforts and actions following the current situation are needed in the form of training and assistance as a form of community service that needs to be done to bridge the existing problems. This community service activity has the aim that teachers can make e-learning teaching materials based on their expertise. The method of implementing this service consists of the planning, implementation and evaluation stages. This service activity was attended by 13 teachers at Bina Mandiri Vocational School and was held from 15 to 20 August 2022 for 5 (five) days offline in the form of training and mentoring. The results of this service activity include: 1) Providing training so that teachers know the competence of their respective fields to develop e-learning teaching materials according to competencies. 2) Can guide teachers to create e-learning teaching materials concepts according to their field of expertise. 3) Assist teachers in making e-learning teaching materials following the concepts that have been made. 4) Can provide knowledge about any platforms used as e-learning teaching materials. This service activity was carried out well, as evidenced by the service participants' reactions after completing it. In addition, activity participants still need similar training using other media or e-learning applications.